2017
DOI: 10.1055/s-0043-100105
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancies in Women Aged 45 Years and Older – a 10-Year Retrospective Analysis in Berlin

Abstract: Over the last five decades, the mean maternal age at birth in Germany has increased steadily from an average age of 27.5 years in 1960 to 30 years in 2014 [1]. The birth-rate of women aged ≥ 40 years has also increased slightly, with 35 559 births in 2014 compared to 34 923, 34 641 and 34 203 in the years 2011 to 2013, respectively [2]. This mirrors the dramatically increasing worldwide rate of women of advanced maternal age giving birth over the last dec

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
(17 reference statements)
2
7
0
3
Order By: Relevance
“…Our analyses showed that the risk of GDM increased by approximately 6% for each year of age. This increase in the risk is in line with findings reported in other publications [ 6 , 31 33 ], independently of other risk factors.…”
Section: Discussionsupporting
confidence: 93%
“…Our analyses showed that the risk of GDM increased by approximately 6% for each year of age. This increase in the risk is in line with findings reported in other publications [ 6 , 31 33 ], independently of other risk factors.…”
Section: Discussionsupporting
confidence: 93%
“…In a 10-year retrospective analysis by Rendtorff et al the caesarean section rate was found to be significantly elevated in women aged >45 years old. 23 Moreover, the authors demonstrated that women with advanced age experienced an increased risk of preterm delivery (28% vs. 11%), preeclampsia, gestational diabetes and premature rupture of membranes. Similarly, in a comparison between 35and 20-year-old parous women, Gareen and colleagues reported that the unadjusted risk ratio for caesarean sectionwas 1.40 [95% confidence limit (CL)=1.18-1.65].…”
Section: Discussionmentioning
confidence: 99%
“…O risco dobra quando a pré-eclâmpsia está presente na gestação. 13,19 É consenso na literatura que a idade materna avançada é fator de risco para o parto cesáreo, [5][6]17…”
Section: Introductionunclassified
“…No grupo de gestantes tardias, a única doença em comum foi DMG,11 e em outro foram as infecções do trato urinário 4. Em um estudo, pré-eclâmpsia, síndrome de HELLP e DMG apareceram como fatores de risco para o trabalho de parto prematuro em mulheres em idade avançada 17. Outro, que envolveu diversos países e 37.787 mulheres com idade igual ou maior a 35 anos, encontrou resultados adversos, incluindo morte materna e desfechos maternos graves em pacientes nessa faixa etária 18.…”
unclassified